2012
DOI: 10.1002/pbc.24055
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of childhood acute lymphoblastic leukemia in Iraq using FTA cards

Abstract: International collaboration via FTA cards may be helpful to improve diagnosis and management of patients with hematological malignancies in low-income and underdeveloped countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…Diagnostically difficult cases were reviewed by an Italian team guided by Dr. Anna Maria Testi (Department of Cellular Biotechnologies and Hematology, University “La Sapienza”, Rome, Italy) via telemedicine sessions . The diagnosis of ALL and AML was confirmed on initial unstained bone marrow (BM) aspiration smears that were transferred from Iraq and stained with May‐Grünwald‐Giemsa and myeloperoxidase at the Department of Pediatrics, Shinshu University School of Medicine . In Jordan, the diagnosis of ALL and AML was confirmed by flow cytometric analysis: CD10, CD19, CD20, CD22, and cytoplasmic CD79a were used for B‐precursor ALL; CD1a, CD2, CD3, CD4, CD5, CD7, CD8, cytoplasmic CD3, and TdT were used for T‐lineage ALL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostically difficult cases were reviewed by an Italian team guided by Dr. Anna Maria Testi (Department of Cellular Biotechnologies and Hematology, University “La Sapienza”, Rome, Italy) via telemedicine sessions . The diagnosis of ALL and AML was confirmed on initial unstained bone marrow (BM) aspiration smears that were transferred from Iraq and stained with May‐Grünwald‐Giemsa and myeloperoxidase at the Department of Pediatrics, Shinshu University School of Medicine . In Jordan, the diagnosis of ALL and AML was confirmed by flow cytometric analysis: CD10, CD19, CD20, CD22, and cytoplasmic CD79a were used for B‐precursor ALL; CD1a, CD2, CD3, CD4, CD5, CD7, CD8, cytoplasmic CD3, and TdT were used for T‐lineage ALL.…”
Section: Methodsmentioning
confidence: 99%
“…All included patients had Iraqi or Jordanian nationality backgrounds. A total of 318 patients with ALL consisted of 264 previously reported ALL cases from five pediatric oncology centers in Iraq: the Children's Welfare Teaching Hospital in Baghdad (a major referral center for childhood cancers in the country), Central Teaching Hospital for Children in Baghdad, Basra Children's Specialty Hospital in Basra, Ibn Al‐Atheer Hospital for Children in Mosul, and Nana‐Kali Hospital for Hemato‐Oncology in Erbil, and 54 patients from KHCC in Jordan. A total of 167 patients with AML consisted of 134 previously reported Iraqi AML cases and 33 from KHCC were evaluated .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted using the QIAamp DNA Blood Mini Kit (Qiagen, Chuo‐ku, Tokyo, Japan), followed by sodium bisulfite treatment using the EZ DNA Methylation Kit (Zymo Research, Irvine, CA, USA) as reported previously . PCR reaction was performed as described previously …”
Section: Methodsmentioning
confidence: 99%
“…The cDNA was used as a template for reverse‐transcriptase PCR (RT‐PCR) and quantitative real‐time PCR with primers and probes listed in Supplementary Table S2. RT‐PCR was performed as reported previously . Real‐time PCR was carried out in an ABI sequence detection system using the Master Mix (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%